Multivariate analysis of right ventricle echocardiographic function parameters for the prediction of outcomes in significant functional tricuspid regurgitation. (8th February 2021) - Travieso Gonzalez, A; Romero Delgado, T; Luque Diaz, TS; Islas, F; Olmos, C; Higueras Nafria, J; Vivas, D; Mahia Casado, P; Vilacosta, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Functional tricuspid regurgitation is a common disease that significantly impairs survival and quality of life. The role of echocardiographic right ventricular (RV) function parameters to detect patients with worse prognosis that may benefit from invasive treatment is still under debate. Methods: 121 consecutive patients with grade III and IV functional tricuspid regurgitation were evaluated. RV function parameters and clinical variables were assessed at baseline, and then patients were prospectively followed-up. The primary endpoint was the combination of death or heart failure (HF) admissions. Comparison of imaging parameters was done using receiver-operating characteristics (ROC) curves. Multivariate logistic regression analysis was preformed to establish independent predictors of outcomes. Results: Median follow up was 27.3 months. 73.6% of the patients were female, and mean age was 80.4 years. 63.6% were grade IV tricuspid regurgitation. In the univariate analysis using the area under the ROC curve (AUC), RV-free wall strain (RVS, AUC = 0.633) and pulmonary artery systolic pressure (PASP, AUC = 0.605) were the best predictors of death and HF admissions, showing better diagnostic performance than tricuspid annular plane systolic excursion (TAPSE), fractional area change (FAC) and tricuspid S' (p < 0.001 for each comparison) (graph 1A). In the multivariate analysis including either clinical and echocardiographic variables, independent predictors of death and HF admissions were Age (OR 1.07, p = 0.029), RVS>-16 (OR 5.0, p = 0.001), Diabetes mellitus (OR 3.0, p = 0.011), eGFR (ml/min, OR 0.96, p = 0.001) and Hemoglobin (g/dL, OR = 0.74, p = 0.048) (table 1). The model including these variables was superior than RVS and PASP alone (AUC 0.884, p < 0.001) (graph 1B), showing high sensitivity (78.8%) and moderate specificity (67.3%). Conclusions: In patients with significant functional tricuspid regurgitation, RVS and PASP show the best performance for the detection of death and HF admissions. A multivariate model including age, diabetes, eGFR, hemoglobin and RVS was superior than the individual imaging parameters.